On the Inscrutability of Logic in Certain Natural Language Contexts - Ruthrof, Horst (Public Journal of Semiotics, 2013)
The paper opens by defining 'logical universality' as the retention of the propositional content of expressions under any enunciative circumstances. Universality in this sense, the paper claims, cannot be demonstrated in the same manner across different discursive domains and sign systems. Unlike in geometry, arithmetic, algebraic and mathematical logic, where logical universality can be shown to be non-controversial, the concept of universality becomes problematic as soon as natural language terms and syntax are employed. The paper shows the main reasons for this difficulty to lie in the extensional features of natural language, which cannot be adequately captured by intentional means. Intentional descriptions are claimed to apply only to semiotically homogeneous sign systems of a formal kind. Natural language expressions, in contrast, are semiotically heterogeneous, or heterosemiotic, characterised as they are by quasi-perceptual ingredients. Nevertheless, the paper argues, there are three cases in which logical universality can be demonstrated to hold in spite of natural language being employed, one of which is strictly technical language. In contrast, culturally fully saturated natural language use is shown to escape the constraints of logical universality as defined, on the grounds that some of its essential features, such as referential background, reference, and deixis, especially in its implicit form, effectively undermine the retention of identical propositional contents across cultures and time.